USE OF HONEY AS NUTRITIONAL AND THERAPEUTICSUPPLEMENT IN THE TREATMENT OF INFECTIOUS DISEASES - Pereira, P.c.m. [UNESP]; Barraviera, B. [UNESP]; Burini, R.c. [UNESP]; Soares, A.m.v.c. [UNESP]; Bertani, M.a. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 1995)
Honey, royal jelly, propolis, materials produced and/or gathered by Apis mellifera honeybees have been used as food and medication for centuries(6,7,8). Although extensively used, honeybee products have become a matter of interest and controversy for years. Honey, well known as healthy and natural food, has shown therapeutic properties in the treatment of digestive, respiratory, cardiac and rheumatic disorders, among others(4). Several studies have reported honey's immunological, antibacterial, antiinflammatory, antipyretic properties besides its importance in terms of energy intake(3,5). Furthermore, honey has proved to possesses wound healing and analgesic actions(1,2). Honey and propolis are also known to be effective in the treatment of respiratory disorders caused by bacteria and fungi which lead to a deterioration of the patient's nutritional and immunological condition(6,7). Thus, a nutritional supplementation with propolis and honey associated with specific treatment can contribute to the patient's recovery.
Keywords: honey; nutritional supplement; Apis mellifera; paracoccidioidomycosis; tuberculosis